Improving the electrochemical performance of ultrahigh-nickel-based layered LiNi0.95Mn0.05O2 cathode through cobalt modification for next-generation high-energy Li-ion batteries - Jinyu Chen; Binbin Chu; Guangxin Li; Tao Huang; Aishui Yu (Electrochemistry Communications, 2023)
Nickel-rich cobalt-free layered cathode materials are expected to meet the urgent demand for high-energy batteries at an adorable cost. However, as the nickel content increases and cobalt content decreases, layered cathode materials suffer from serious structure degradation and capacity fade during cycling. The large amount of residual lithium in nickel-rich materials also brings difficulties to industrial manufacturing and challenges battery safety. In this work, well-formed crystal cobalt-contained coatings with surface cobalt-doped ultrahigh-nickel-based layered LiNi0.95Mn0.05O2 cathode material is synthesized through solid solution and post-heat treatment with Co(OH)2, during which the residual lithium is significantly consumed. The optimized sample acquired at 650 ℃ shows an increased discharge capacity of 221.2 mAh g−1 from 219 mAh g−1 of the pristine one at 0.1 C and the capacity retention is enhanced from 72.6% to 83.2% for 100 cycles at 0.5 C.